Urine Drug Screening for Isolated Marijuana Use in Labor and Delivery Units. Issue 4 (9th October 2022) - Rubin, Alexandra; Zhong, Lydia; Nacke, Lauren; Woolfolk, Candice; Raghuraman, Nandini; Carter, Ebony; Kelly, Jeannie
Abstract : Urine drug screening on a labor and delivery unit for isolated marijuana use rarely predicts other substance use. Abstract : Isolated marijuana use is frequently used as an indication for urine drug screening in labor and delivery units. We aimed to identify the results of urine drug screening in a labor and delivery unit for isolated marijuana use. This retrospective cohort study reviewed data from patients admitted for delivery at an urban academic center from January 1, 2020, to December 31, 2020. Patients undergoing urine drug screening for isolated marijuana use were more likely to be younger (median age 25 vs 29 years, P <.001), more often Black (adjusted odds ratio [aOR] 2.58, 95% CI 1.94–3.41), and more likely to have public insurance (aOR 1.54, 95% CI 1.21–1.95). A few (5/338, 1.5%) urine drug screening tests performed for isolated marijuana use were positive for substances besides marijuana. Most patients (177/197, 89.8%) with a urine drug screening test result that was positive for marijuana were reported to the state child abuse hotline. The utility of isolated marijuana use as a criterion for urine drug screening thus appears limited in benefit but rife with inequitable potential to harm.